2022
DOI: 10.1001/jamapediatrics.2021.4248
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Routine Childhood Vaccinations—Identifying Gaps and Informing Solutions

Abstract: On March 11, 2020, the World Health Organization declared COVID-19 a global pandemic. The United States declared a national emergency and, on March 18, 2020, the American Academy of Pediatrics issued guidance advising pediatricians to restrict preventive care visits to younger children requiring immunizations. Pediatric primary care visit volumes precipitously declined. A growing literature is helping to define this impact and raise questions about how best to address the consequences of that lost care.In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Condition is much worse in developing countries [e.g., In India, BCG and Pentavalent missed doses were 1 lakh and 2 lakh, respectively, in March 2020 ( 124 ), and in Pakistan, those who missed a dose of measles and polio were 40 and 50 million, respectively, during the same period] ( 125 ). Five articles ( 16 , 17 , 46 , 63 , 71 ) in the present review have shown the disruption of routine immunization or other health services as one of the negative factors/hindrances for universal childhood COVID vaccination.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Condition is much worse in developing countries [e.g., In India, BCG and Pentavalent missed doses were 1 lakh and 2 lakh, respectively, in March 2020 ( 124 ), and in Pakistan, those who missed a dose of measles and polio were 40 and 50 million, respectively, during the same period] ( 125 ). Five articles ( 16 , 17 , 46 , 63 , 71 ) in the present review have shown the disruption of routine immunization or other health services as one of the negative factors/hindrances for universal childhood COVID vaccination.…”
Section: Discussionmentioning
confidence: 80%
“…The COVID-19 pandemic has caused a huge disruption of the healthcare delivery services since the beginning of the pandemic and COVID vaccination also caused extra stress on the already overburdened healthcare system which lacks sufficient manpower, resources, and logistics, especially for lower economic countries ( 46 , 55 , 63 , 71 , 123 ). It has been reflected by a report of UNICEF that in 2020 number of missed doses of routine vaccines was the highest globally since 2009 ( 123 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some have advocated for converting sick visits to AWC visits, when possible. 10 Tiered approaches to outreach, including home visitation, may also be warranted. 21 …”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 6 Following the pandemic shut-down, thousands of AWC appointments were cancelled or delayed and vaccination administration rates declined. 7 , 8 , 9 Black and Latinx vaccination rates were found to be disproportionately worsening, 9 , 10 creating an imperative to address structural racism with intentional and deliberate intervention. 11 , 12 Additionally, increasing rates of obesity and depression have heightened the importance of AWC preventative services.…”
mentioning
confidence: 99%
“…However, vaccine hesitancy has also increased so the proportion of children who receive their primary vaccine series on schedule is declining. 13 Jang et al 7 highlight the importance of ensuring that children with CeD complete their routine childhood vaccinations, especially the pneumococcal series (PCV13/PCV15/PCV20). Furthermore, their data raises the question whether children with CeD are a population who should receive pneumococcal polysaccharide vaccine (PPSV23).…”
mentioning
confidence: 99%